The Sage of Sages: T. C. Chao's Christology in Yesu Zhuan - Xu, Ximian (Studies in world christianity, 2017)
T. C. Chao (Zhao Zichen, 1888-1979) was a leading Chinese theologian of the twentieth century. His Yesu Zhuan is a well-known book in China and accepted by many Chinese people as a way to know who Jesus is. Given this, this article will examine Chao's Christology in Yesu Zhuan. It will first introduce the historical context of Yesu Zhuan, including national crisis, cultural crisis and anti-Christian movements. Then, Chao's purpose and the methodology of writing Yesu Zhuan will be elaborated, which will be followed by a theological appraisal of Chao's methodology and Christology in Yesu Zhuan. By so doing, the article will demonstrate that under the influence of Western liberal theology and with the effort to indigenise Christianity in China, Chao actually portrays a 'Jesus' who is the most prominent Sage, the Sage of sages. That means he delineates a possible way in which Christian faith may be understood in Chinese culture. However, the 'Jesus' in Yesu Zhuan is a mere human being without divine nature. In the end, the Christology in Yesu Zhuan diametrically contradicts Chalcedonian Christology.